Mapping information systems maturity: the case of the Portuguese hospitality industry - Nuno António; Gustavo Sá (Tourism & Management Studies)
Hospitality is a highly competitive market that struggles to improve its performance. Today, the use of technology is a critical factor for more efficient performance. To understand the perception that decision-makers have of information systems’ influence and importance in their organizations, we conduct a case study in Portugal. The objective was to assess information systems' maturity level of independent hotels and small hotel chains, mapping the level to the hotel's characteristics. We surveyed 86 companies, representing a total of 195 hotels.